Nimodipine augments cerebrovascular reactivity in aging but runs the risk of local perfusion reduction in acute cerebral ischemia - Kecskés, Szilvia; Menyhárt, Ákos; Bari, Ferenc; Farkas, Eszter (Frontiers in Aging Neuroscience, 2023)
The efficacy of cerebrovascular reactivity (CVR) is taken as an indicator of cerebrovascular health. We found that CVR tested with the inhalation of 10 % CO2 declined in the parietal cortex of 18-20-month-old rats. The CVR deficit in old rats was coincident with cerebrovascular smooth muscle cell and astrocyte senescence, revealed by the immuno-labeling of the cellular senescence marker p16 in these cells. In a next series of experiments, CVR was severely impaired in the acute phase of incomplete global forebrain ischemia produced by the bilateral occlusion of the common carotid arteries in young adult rats. In acute ischemia, CVR impairment often manifested as a perfusion drop rather than blood flow elevation in response to hypercapnia. Next, nimodipine, an L-type voltage-gated calcium channel antagonist was administered topically to rescue CVR in both aging, and cerebra ischemia. Nimodipine augmented CVR in the aged brain, but worsened CVR impairment in acute cerebral ischemia. A careful evaluation of benefits and side effects of nimodipine is recommended, especially in acute ischemic stroke.